(untitled) (REMUNOM, 2024)
This article is a study on the Brazilian supplementary health system through an analysis on its regulation and the (ir)regularity of the legal relationships before its validity. In sum, after the publication of uncodified legislation n.º 9.656/1998 and n.º 9.961/2000, the private sector of health assistance was regulated through the standardization of services and economical criteria stipulated by providers. The aim is to convey the idea of equity between the parts. Therefore, through deductive method and literature search, this study questions the regularity of the relationships established before these enactments. Additionally, its objective is to highlight the asymmetry between the users assisted by those laws when compared to adherents of contracts before them, as well as planning to alert those individuals in possible legal loopholes in their terms of service.